PENGARUH NILAI TUKAR KURS, PENANAMAN MODAL DALAM NEGERI (PMDN), DAN PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 1999-2018 - Dessy Triaz Wulandari; Aris Soelistyo; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2020)
Economic growth is a long-term economic problem that is influenced by various factors in implementing economic development. The purpose of this study was to analyze the effect of exchange rates, domestic investment, and government spending in the education sector on economic growth in Indonesia. The analysis technique used in this study is the Multiple Linear Regression technique. The research uses secondary data sources from the official Statistics Indonesia website and from previous research journals. The period used in this study was 20 years starting from 1999 - 2018. The results of the study showed that the variable exchange rate, domestic investment, and government spending in the education sector simultaneously and partially had a positive and significant effect on economic growth in Indonesia.